2017
DOI: 10.1001/jamaneurol.2016.5755
|View full text |Cite
|
Sign up to set email alerts
|

Association of In Vivo [18F]AV-1451 Tau PET Imaging Results With Cortical Atrophy and Symptoms in Typical and Atypical Alzheimer Disease

Abstract: IMPORTANCE Previous postmortem studies have long demonstrated that neurofibrillary tangles made of hyperphosphorylated tau proteins are closely associated with Alzheimer disease clinical phenotype and neurodegeneration pattern. Validating these associations in vivo will lead to new diagnostic tools for Alzheimer disease and better understanding of its neurobiology.OBJECTIVE To examine whether topographical distribution and severity of hyperphosphorylated tau pathologic findings measured by fluorine 18-labeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
216
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(254 citation statements)
references
References 46 publications
37
216
0
1
Order By: Relevance
“…Previous studies have shown that individuals presenting with the visual variant of AD, PCA, have proportionately more regional atrophy, cortical thinning and tau deposition in the occipitoparietal regions than hippocampi and other medial temporal structures compared to those with typical memory led AD 24, 25, 26. Our imaging findings are broadly in keeping with these, with the PCA patients having larger hippocampal and small parietal lobe volumes than patients with typical AD.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown that individuals presenting with the visual variant of AD, PCA, have proportionately more regional atrophy, cortical thinning and tau deposition in the occipitoparietal regions than hippocampi and other medial temporal structures compared to those with typical memory led AD 24, 25, 26. Our imaging findings are broadly in keeping with these, with the PCA patients having larger hippocampal and small parietal lobe volumes than patients with typical AD.…”
Section: Discussionsupporting
confidence: 87%
“…These tau-PET findings of hemispheric asymmetry are particularly valuable because autopsy studies are typically performed with only one hemisphere, and hence do not allow the assessment of asymmetry in tau pathology. The fact that we looked at tau in both hemispheres, and that it seems to match asymmetry in grey matter atrophy and FDG hypometabolism, supports an association between tau deposition and cerebral atrophy [13, 46]. …”
Section: Resultsmentioning
confidence: 62%
“…This may suggest that beta-amyloid deposition in these latter patients may instead reflect diffuse plaques consistent with pathological aging. Of four PiB(+) patients that have previously been reported in three previous studies [22, 33, 37], one patient similarly did not show any evidence for elevated ligand uptake [22], although this study used the [ 18 F]THK-5351 ligand.…”
Section: Discussionmentioning
confidence: 99%